Integration Of Performance Assessment And Achievement-Based Compensation In Improving Employee Productivity - Muhamad Arsy Trisdianto; Sudarmoy; Resti Dewi Astuti; Nur Azilah; Ulfa Hidayatunnikmah (Journal Informatic, Education and Management (JIEM), 2025)
This study examines the effectiveness of an integrated performance appraisal system in determining employee compensation, using a case study of Flip Indonesia. Performance appraisal and compensation are two critical components of human resource management that are closely interrelated. The research employs a quantitative descriptive approach, utilizing evaluation scores from four key aspects: goal setting, appraisal, scoring, and measurable compensation. The objective of this study is to identify the extent to which system integration can enhance employee motivation, productivity, and retention. The findings indicate that the system implemented by Flip Indonesia received high scores across all evaluation aspects, with measurable compensation achieving the highest score of 4.3. The integration of goal setting, performance evaluation, and scoring prior to determining compensation has proven effective in fostering transparency and fairness. These results reinforce the argument that a systematic, data-driven appraisal system can promote employee loyalty and support the achievement of strategic organizational goals. Therefore, this model may serve as a reference for other organizations in designing sustainable, performance-oriented HR policies.